Constitutional Concept of the Village Chief Office Term Extension and It's Legal Implications - Pratiwi, Fita Dwi; Wardana, Dodi Jaya (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
The demonstration at the DKI Jakarta DPR Building demanding an extension of the village chief's term of office has reaped many pros and cons in the community. The reason is because the position of village chief for 6 (six) years is considered too fast. In fact, regulations and laws relating to villages were born in response to the large influence of village heads during the New Order era. One of these regulations is to limit the term of office. The aim of this research is to find out and analyze whether the extension of the village chief's term of office is in accordance with the constitutional system, the principles of the rule of law and democracy in Indonesia. The method used is a normative juridical approach, based on descriptive analysis based on historical cases and regulations. This approach is intended because in the historically, there is a theory that can reduce authority by using law to extend the term of office of the village chief. In fact, regulations, legislative regulations have actually been designed with provisions regarding the maximum survival limit for village chiefs. However, in reality, this clause is often violated. This is made worse by the fact that it is the village chief who appoints each individual within the village framework, not the community. With these demands, it is the community who should determine whether the demands given need to be resolved or not. In this research the author concludes that extending the term of office of village chiefs is contrary to the constitutional system, the principles of the rule of law and democracy in Indonesia because the ideals of law and the constitution require limitations on power to avoid abuse of authority by state officials. If this request is granted, democracy in Indonesia will decline.